PENGUATAN KOMITMEN KERJA MELALUI PENINGKATAN MOTIVASI YANG DIPENGARUHI OLEH BUDAYA DAN LINGKUNGAN KERJA - I Nyoman Marayasa; Mukrodi Mukrodi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The results will not betray effort, it is a real expression, that every success is the result of hard work, ability, intelligence, and sacrifice. This means that at work requires a committed attitude. Namely, a determination, sincerity, and responsibility for the trust received. Thus, every behavior is obedience to rules, obedience to orders, and compliance with procedures. The employee model with this attitude has a significant effect on the achievement of organizational goals. This study is interested in expressing the attitude of commitment and the variables that influence it. The research method used is quantitative, descriptive analysis, and path analysis. The results showed that the organizational culture variable was the dominant factor in commitment. Even organizational culture can increase morale (motivation) which has an impact on strengthening work commitment. In addition, the work environment variable has a weak relationship in explaining work motivation and commitment.